The Work of The Graduate of Riga Polytechnic Institute Augusts Baumanis (1883–1966) In Engineering Science and Pedagogy - Zigmunde, Alīda (History of Engineering Sciences and Institutions of Higher Education, 2019)
Engineer, entrepreneur and teacher Augusts Baumanis (1883–1966) is one of the graduates of Riga Polytechnic Institute (RPI) who were renown in the 1920s and 1930s. Latvia’s growth without his activities is unthinkable. After graduating from the Department of Chemistry (1913) of RPI, he worked in Russia. In 1919, after returning to Latvia, A. Baumanis became involved in oil production and in export of wooden boards. From 1928 to 1931, he travelled around South Africa with his family and worked in gold mines. After returning to Latvia, he started to work as a teacher. The aim of the article is to reveal the life of engineer A. Baumanis, to introduce readers to the Latvian entrepreneur and to analyse the problems he had to face in business and pedagogy during the interwar period.